Computation of conventional and alternative jet fuel sensitivity to lean blowout. (April 2022) - Hasti, Veeraraghava Raju; Kundu, Prithwish; Som, Sibendu; Won, Sang Hee; Dryer, Frederick L.; Gore, Jay P.
Abstract: Large Eddy Simulations (LES) are performed to compute the sensitivity of a conventional (A-2) and an alternate bio-jet (C-1) fuel to Lean Blowout (LBO). A realistic aviation gas turbine engine combustor configuration is considered. Reliable experimental LBO data and OH∗ chemiluminescence data for the conventional and alternate jet fuel in the combustor configuration have recently become available. The present work utilizes a highly automated, on-the-fly meshing strategy, along with adaptive mesh refinement, to demonstrate the feasibility of capturing the realistic combustion processes. A Lagrangian framework, with initial conditions specified using measurements of spray statistics, is used to model the fuel spray. Newly developed compact reaction mechanisms based on fuel surrogates are validated for the A-2 and the C-1 fuels. The compact reaction mechanisms are implemented using a detailed finite rate chemistry solver. Spray statistics computed by the present LES simulations compare well with available measurements at stable flame conditions near the lean blowout limit. The computed shape of the stable flame as represented by line integrated OH concentrations compares well with the experimental OH∗ chemiluminescence data. Lean blowout is reached by gradually decreasing the fuel flow rate in the computations, similar to that in the experiments. The results of the LES simulations effectively capture the fuel composition effects and estimate the sensitivity of the LBO limits to the fuel type. The computed trends in LBO limits agree within engineering accuracy with the experimental results for conventional and alternative aviation fuels. The methodology for predicting the fuel composition effects on the lean blowout limits in a fully resolved realistic, complex combustor is established for the first time. Highlights: A fully resolved practical combustor is simulated using autonomous meshing and LES. A comprehensive computational methodology established for the simulation of Lean Blowout (LBO). LES accurately predicted the fuel sensitivity to LBO. LES results agree reasonably well with experiments for LBO limits between conventional and alternative fuels. Simulations highlight differences in the flame structure between conventional and alternative fuels.